Constant Weight Space-Time Codes for Dimmable MIMO-VLC Systems - Jia-Ning Guo; Jian Zhang; Yan-Yu Zhang; Gang Xin; Lin Li (IEEE Photonics Journal)
Visible light communication(VLC), which combines communication and illumination, is regarded as a potential wireless communication. For illumination requirements of VLC systems, dimming control is a significant function. Many schemes have been proposed for multi-input multi-output (MIMO) VLC systems or dimmable VLC systems, but few schemes combine the two. The dimming control scheme that has been proposed for MIMO-VLC systems in the reference still has a probability for improvement in spectral efficiency and error performance. This paper proposes a dimming control scheme that utilizes the constant weight space-time codes (CWSTC) to improve spectral efficiency and error performance for MIMO-VLC systems. Simultaneously, we also present the codeword structure and a low implementation complexity detection algorithm for the scheme. Finally, performance analysis and simulation results provide comparisons between the proposed scheme and other existing dimming control schemes.